Microbes in the Era of Circadian Medicine - Costantini, Claudio; Renga, Giorgia; Sellitto, Federica; Borghi, Monica; Stincardini, Claudia; Pariano, Marilena; Zelante, Teresa; Chiarotti, Flavia; Bartoli, Andrea; Mosci, Paolo; Romani, Luigina; Brancorsini, Stefano; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The organisms of most domains of life have adapted to circadian changes of the environment and regulate their behavior and physiology accordingly. A particular case of such paradigm is represented by some types of host-pathogen interaction during infection. Indeed, not only some hosts and pathogens are each endowed with their own circadian clock, but they are also influenced by the circadian changes of the other with profound consequences on the outcome of the infection. It comes that daily fluctuations in the availability of resources and the nature of the immune response, coupled with circadian changes of the pathogen, may influence microbial virulence, level of colonization and damage to the host, and alter the equilibrium between commensal and invading microorganisms. In the present review, we discuss the potential relevance of circadian rhythms in human bacterial and fungal pathogens, and the consequences of circadian changes of the host immune system and microbiome on the onset and development of infection. By looking from the perspective of the interplay between host and microbes circadian rhythms, these concepts are expected to change the way we approach human infections, not only by predicting the outcome of the host-pathogen interaction, but also by indicating the best time for intervention to potentiate the anti-microbial activities of the immune system and to weaken the pathogen when its susceptibility is higher.